From Rhetoric to Regulation: EMFA and Media Concentration in the Digital Age - Tanja Kerševan (Rivista Italiana di Informatica e Diritto)
This article examines the evolving political discourse and practices surrounding media pluralism within the European Union (EU) in light of the European Media Freedom Act (EMFA), which mandates that Member States evaluate the impact of media market concentrations on media pluralism. Through analysis of key EU legislative and policy texts the article explores how media concentration is addressed, with a particular focus on two smaller Member States (Croatia and Slovenia) where outdated laws and the lack of data to assess media pluralism pose significant challenges. The findings highlight the difficulties in ensuring the effective and harmonised implementation of EMFA provisions across the EU, especially in the face of digital platforms’ growing dominance over content distribution and public discourse. The article argues that without clear, comprehensive guidance and coordinated efforts to ensure consistent enforcement across Member States, the regulation may fall short in effectively addressing the risks posed to media pluralism, particularly in the rapidly evolving digital environment.